, мне решить это. Проблема заключается в приложении

Пожалуйста, помогите мне решить это. Проблема заключается в приложении

    5^x=t, t>0

     

    ОТВЕТ: -1 и 1

    5^x=1/5

    25^x*5-26*5^x+5=0

    Из чего следует, что х=0

    x=1

    5^x=5

    3*2^(2x)+6^(x)-2*3^(2x)=0      /:3^(2x)≠0

    (2/3)^x=t, t>0

    6^x=0

    2)

     

    6^2x+6-6^2x=0

    3t^2+t-2=0

    t=(26-24)/10=1/5

    5t^2-26t+5=0

    получим:

    D=1+24=25>0

    t=(26+24)/10=5

    D=676-100=576>0

    ОТВЕТ:  1

    t=(-1-5)/6=-1  (не подходит)

  • 1)

    (2/3)^x=2/3

    x=-1

    3*(4/9)^x+(2/3)^x-2=0

     

  • 3*2^2x+6^x-2*3^2x=0

     

    t=(-1+5)/6=2/3

     

  • x=1